2022
DOI: 10.1177/09603271211069038
|View full text |Cite
|
Sign up to set email alerts
|

A comprehensive gene expression profile of allergic rhinitis-derived nasal fibroblasts and the potential mechanism for its phenotype

Abstract: Background Allergic rhinitis (AR) is a common immunoglobulin E-mediated immune response involved various cell types, while the role of nasal fibroblasts (NFs) in the pathogenesis of AR is less understood. Purpose The study aimed to uncover the gene expression profile of AR-derived NFs and the potential mechanism for the changed phenotype of AR-NFs. Research Design The primary NFs were isolated from 3 AR patients (AR-NFs) and 3 controls (Ctrl-NFs), and the proliferation, migration and interleukins production ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 47 publications
0
7
0
Order By: Relevance
“…We identified BARX1 as a key regulator involved in NSCLC progression by combining the ESTIMATE score with the transcriptome-based differently expressed genes analysis, and here mainly focused on its oncogenic role and regulation. Although a recent study showed that silencing BARX1 resulted in downregulated production of interleukins in allergic rhinitis-derived nasal fibroblasts, the exact role of BARX1 in tumor immune response remains to be elucidated [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…We identified BARX1 as a key regulator involved in NSCLC progression by combining the ESTIMATE score with the transcriptome-based differently expressed genes analysis, and here mainly focused on its oncogenic role and regulation. Although a recent study showed that silencing BARX1 resulted in downregulated production of interleukins in allergic rhinitis-derived nasal fibroblasts, the exact role of BARX1 in tumor immune response remains to be elucidated [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have been conducted to identify candidate genes associated with rhinitis. However, these studies were conducted with limited sample numbers and require further evaluation [ 9 , 26 ]. As such, the molecular mechanisms underlying AR remain unclear.…”
Section: Discussionmentioning
confidence: 99%
“…For example, primary nasal fibroblasts isolated from patients with AR showed higher proliferation and migration abilities and increased expression of interleukin (IL)‐33 and IL‐6 compared to controls. 6 Furthermore, it has been demonstrated that human fibroblasts from patients with AR release thymic stromal lymphopoietin (TSLP) in response to IL‐17A. Since IL‐17A has been implicated in the pathogenesis of AR and TSLP modifies the immune response toward a Th2 phenotype, these results suggest that fibroblasts play a role in the development of AR.…”
Section: Cox‐2 Expressionmentioning
confidence: 99%
“…Several studies have demonstrated that fibroblasts release proinflammatory mediators involved in the molecular mechanisms present in the airways of patients suffering from AR. For example, primary nasal fibroblasts isolated from patients with AR showed higher proliferation and migration abilities and increased expression of interleukin (IL)‐33 and IL‐6 compared to controls 6 . Furthermore, it has been demonstrated that human fibroblasts from patients with AR release thymic stromal lymphopoietin (TSLP) in response to IL‐17A.…”
Section: Cox‐2 Expressionmentioning
confidence: 99%